2009
DOI: 10.1007/s10661-009-1078-3
|View full text |Cite
|
Sign up to set email alerts
|

Total petroleum hydrocarbons and trace heavy metals in roadside soils along the Lagos–Badagry expressway, Nigeria

Abstract: This study reports the level of total petroleum hydrocarbons (TPH) and trace heavy metals (lead, copper, and cadmium) in soil samples collected randomly from Iyana-Iba garage, Lagos State University bus stop, Adeniran Ogunsanya College of Education bus stop, and a control site off Lusada-Atan road, near Crawford University, Igbesa, Ogun state. TPH was estimated gravimetrically after Soxhlet extraction and column clean up, while soil metals were determined by atomic absorption spectrometry using mineral acid di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…Lead level found at N-5 is much higher than those detected by other workers (Bakirdere and Yaman 2008;Swaileh et al 2004;Herngren et al 2006;Adeniyi and Owoade 2009). But it is still lower than some previous studies (Abdul-Wahab 2004;Kakulu 2003).…”
Section: Resultscontrasting
confidence: 53%
“…Lead level found at N-5 is much higher than those detected by other workers (Bakirdere and Yaman 2008;Swaileh et al 2004;Herngren et al 2006;Adeniyi and Owoade 2009). But it is still lower than some previous studies (Abdul-Wahab 2004;Kakulu 2003).…”
Section: Resultscontrasting
confidence: 53%
“…And the TPH levels were higher compared to other petrochemical areas (Adeniyi and Afolabi 2002;Adeniyi and Owoade 2009;Iturbe et al 2004;Soukup et al 2007). Results also indicated that the soil TPH concentrations varied among three land-use types ( Table 1).…”
Section: Resultsmentioning
confidence: 86%
“…In particular, soil contamination by heavy metals has become a serious problem in many parts of the world [11][12][13][14][15][16][17]. Heavy metals released into biosphere are not subject to degradation processes and, therefore, they remain in the environment almost indefinitely causing accumulation phenomena.…”
Section: Introductionmentioning
confidence: 99%